Crisis and recovery learning from COVID-19's economic impacts and policy responses in East Asia - World Bank
More than three years after the first COVID-19 case was discovered in the East Asia and Pacific (EAP) region, it is time to take stock of the lasting effects—and opportunities—of the pandemic and identify which policies may have helped stem the economic losses suffered by households and firms. To do so, this regional report examines the economic impact of the COVID-19 pandemic on households and firms in six countries: Cambodia, Indonesia, Malaysia, Mongolia, the Philippines, and Vietnam. This volume examines: (a) the links between impacts on firms and households, in particular through the employment channel, and (b) governments’ fiscal responses to the COVID crisis, through transfers, subsidies, and taxes. It identifies and explains changes in household well-being by examining the economic effects of the pandemic on labor markets. As the source of employment and wage income, businesses have a direct role in determining jobs and earnings, and, indirectly, welfare, poverty, and inequality. When faced with a shock, firms responded by adjusting employment, reducing wages, increasing prices, and reducing services provided. All of these channels directly affected households’ wellbeing. For this reason, the report focuses on firms in addition to households. Governments responded through various instruments, providing transfers and subsidies and lowering the tax burden to both households and firms.
Includes bibliographical references.
Chapter 5 written by Prof. Karl Jandoc together with Ms. Irene Jo Arzadon.